Collaborative Filtering Strategy for Product Recommendation Using Personality Characteristics of Customers - Aguiar, Janderson Jason B.; Fechine, Joseana Macêdo; Costa, Evandro de Barros (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2020)
Research indicates that people can receive more useful product recommendations if the filtering process considers their personality. In this paper, we propose a hybrid strategy for Recommender Systems (using matrix factorization and personality-based neighborhood) to recommend the best products calculated for a particular customer (user). The proposed user profile used in the definition of the neighborhood involves these three personality models: Big Five (or OCEAN, or Five-Factor Model), Needs, and Values. We experimented with data from more than 10,000 Amazon customers. We inferred their personality characteristics from the analysis of reviews via IBM Watson Personality Insights. The results indicated that the proposed strategy's performance was better than that of the state-of-the-art algorithms analyzed. Besides, there was no statistical difference between using only the Big Five model or using it together with the Needs and Values models.